Kepemimpinan Yang Amanah Dan Perubahan Insfrastruktur Desa Pagar Merbau III Kecamatan Lubuk Pakam - Aisah, Mira Nur; Aslami, Nuri (Universitas Labuhanbatu, 2022)
This study aims of course to inform the description of the system of each work in the field within the scope of the village fence Merbau III with a mandate to the responsibility of a village head as a leader in a village scope that involves changes in the management of a village environment for the better. The research method used is a qualitative descriptive method. Where, the function of a village head is or can be said to be the role of the village head is to always provide attention, motivation, can affect the members, and of course provide the best facilities. With this, the technique of data collection or analysis is through literature study as a Supporting Role. Therefore, the results of this study is an effort to increase participation and programs to the community, one of which is called BUMDes (village-owned enterprises). Of course, a leader can provide the best things by improving the mindset of the community with useful and positive things. A leader in the administration of government in a work area that in the performance of its duties obtain the authority of the Government of the Regent to provide handling as a matter of regional autonomy and to hold a general task that is the responsibility of a village head in government.